PROFIL PENGGUNAAN OBAT PADA PASIEN COVID-19 DI SALAH SATU RUMAH SAKIT DI BANJARMASIN - Yusrinie Wasiaturrahmah; Aditya Maulana Perdana Putra; Nahdha Nahdha; Nahdiya Rahmah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Coronavirus 19, Knowing as COVID-19, is a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 treatment is still limited to supportive and oxygen therapy. The use of drugs is on the complaints felt by patients and comorbidities. This study aims to look at drug use profiles in COVID-19 patients. This research was included in descriptive research with a retrospective cross-sectional design. This research data was the entire prescription sheet and medical records of COVID-19 patients for March-August 2020 that meet the inclusion criteria. The result from collecting COVID-19 patient data for March-August 2020 obtained 114 medical records that met the criteria for research inclusion. Research Result: Characteristics of study subjects of the male sex are more infected with COVID-19. The age range with the highest number of COVID-19 patients was 46-55 years. Treatment profiles often used in COVID-19 patients are Supplements and Vitamins for 6538 prescriptions and Antibiotics for 2813 prescriptions. The most prescribed supplements and vitamins are Vitamin C, Lakto B, Zinc, and Vitamin C. The most prescribed antibiotics are Azithromycin, Meropenem, and Levofloxacin. The conclusion obtained in this study is that Supplements and vitamins, and Antibiotics are the most prescribed drug class.